(untitled) (Bangladesh Journal of Pharmacology, 2013)
This study was designed to evaluate bronchodilator and cardio-tonic effects of Urginea indica to provide rational for these medicinal uses. U. indica bulb extract was studied on rabbit tracheal and guinea-pig atrial preparations mounted in tissue baths under simulated physiological conditions. U. indica inhibited carbachol (1 µM) and K+ (80 mM)-induced contractions in rabbit trachea, similar to dicyclomine, suggesting the presence of anticholinergic and calcium channel blocking (CCB) mechanisms in U. indica. Anticholinergic and CCB effects of U. indica were respectively confirmed when it shifted the carbachol and Ca2+ concentration-response curves rightwards, similar to dicyclomine. U. indica (0.01-1 mg/mL) increased force of guinea-pig atrial contractions without significantly affecting the rate. These data, indicating that U. indica possesses the bronchodilator activity possibly mediated through a combination of anticholinergic and Ca2+ antagonist mechanisms together with selective positive inotropic effect, provide rational for medicinal applications of U. indica in airways and cardiac disorders.